A Review Essay on Alvin Roth’s Who Gets What—and Why - Glaeser, Edward L. (Journal of Economic Literature, 2017)
Alvin Roth's Who Gets What—And Why provides a richly accessible introduction to his pioneering work on market design. Much of economics ignores the institutions that allocate goods, blithely assuming that the mythical Walrasian auctioneer will handle everything perfectly. But markets do fail and Roth details those failures, like the market for law clerks that unravels because clerks and judges commit to each other too quickly. Roth combines theory and pragmatic experience to show how the economist can engineer successful markets. He has even enabled welfare-improving trades in kidney exchanges, where law and social repugnance forbids cash payments. (JEL C78, D47)